Soft magnetic material and manufacturing method of them
By rapidly treating an alloy with an amorphous phase and specific elemental compositions, a Fe-based nanocrystalline soft magnetic material is created, addressing the challenges of maintaining high saturation magnetic flux density and low coercivity, and achieving effective performance in magnetic components.
Patent Information
- Application Number
- JP2023175416
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-10-10
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2043-10-10
AI Technical Summary
Existing soft magnetic materials face challenges in maintaining high saturation magnetic flux density while suppressing crystal coarsening during heat treatment, and achieving low coercivity.
A Fe-based nanocrystalline soft magnetic material is developed by rapidly treating an alloy with an amorphous phase, containing appropriate amounts of Si, Ni, and other elements, to achieve a composition of Fe 100-x-y-z-w B x Ni y Si z M w, where M is one or more elements selected from Nb, Mo, Ta, W, Co, and Sn, and specific atomic percentages are maintained to ensure high saturation magnetic flux density and low coercivity.
The resulting soft magnetic material achieves both high saturation magnetic flux density and low coercivity, making it suitable for use in magnetic components such as motors and reactors.
Smart Images

Figure 2025065896000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a soft magnetic material and a method for producing the same. [Background technology]
[0002] To improve the performance of components such as motors and reactors, the soft magnetic materials used in the core of these components must have both high saturation magnetic flux density (high torque) and low coercive force (low loss).
[0003] Examples of soft magnetic materials with high saturation magnetic flux density include electromagnetic steel sheets, Fe-based nanocrystalline soft magnetic materials, etc. Fe-based nanocrystalline soft magnetic materials are soft magnetic materials whose main component is Fe, with nanocrystals dispersed within the material.
[0004] For example, Patent Document 1 describes a compound having the general formula Fe 100-a-b-c-d-e Ni a M b B c M' d M'' e (wherein M represents Si, Ge, Ga, M' represents Nb, Mo, W, Ta, Zr, Hf, Ti, and M'' represents one or more elements selected from V, Cr, Mn, and Al; a, b, c, d, and e represent atomic % and satisfy 0.5≦a≦5, 0≦b≦10, 9≦c≦16, 1≦d≦6, 0≦e≦2, and 16≦a+b+c+d+e≦25, respectively).
[0005] Patent Document 2 describes a method for producing an alloy having a composition represented by the following composition formula 1 or 2 and having an amorphous phase, and a method for producing an alloy comprising heating the alloy at a heating rate of 10° C. / sec or more and holding the alloy at a temperature equal to or higher than the crystallization onset temperature and lower than the formation onset temperature of an Fe-B compound for 0 to 80 seconds, wherein the composition formula 1 is Fe 100-x-y B x M yand M is at least one element selected from Nb, Mo, Ta, W, Ni, Co, and Sn, and x and y satisfy 10 ≦ x ≦ 16 and 0 ≦ y ≦ 8 in atomic %, and the composition formula 2 is Fe 100-a-b-c B a Cu b M’ c and M’ is at least one element selected from Nb, Mo, Ta, W, Ni, and Co, and a, b, and c satisfy 10 ≦ a ≦ 16, 0 < b ≦ 2, and 0 ≦ c ≦ 8 in atomic %, and a method for manufacturing a soft magnetic material is described.
Prior Art Documents
Patent Documents
[0006]
Patent Document 1
Patent Document 2
Summary of the Invention
Problems to be Solved by the Invention
[0007] As described above, for improving the performance of magnetic components such as motors and reactors, it is important to achieve both a high saturation magnetic flux density and a low coercive force for the soft magnetic material of the core part.
[0008] Since the main component of the Fe-based nanocrystalline soft magnetic material is Fe, it has a high saturation magnetic flux density. The Fe-based nanocrystalline soft magnetic material is obtained by heat treating (also called "annealing") an alloy having an amorphous phase. If the Fe content in the alloy having an amorphous phase is high, a crystalline phase (α-Fe) is likely to be generated from the amorphous phase when heat treating is performed, and the crystalline phase is likely to grow and become coarse. Therefore, an element that suppresses grain growth is added to the material. However, the Fe content in the material decreases by the amount of the element added, so the saturation magnetic flux density of the material decreases. For these reasons, when the main component of a soft magnetic material is Fe, it is difficult to maintain a high saturation magnetic flux density while suppressing the coarsening of the crystalline phase during heat treatment and maintaining a low coercive force.
[0009] Therefore, an object of the present invention is to provide a soft magnetic material that achieves both high saturation magnetic flux density and low coercive force, and a method for manufacturing the same. [Means for solving the problem]
[0010] The inventors have investigated various means for solving the above problems and have found that an Fe-based nanocrystalline soft magnetic material having high saturation magnetic flux density while maintaining low coercivity can be obtained by rapid heat treatment of an alloy having an amorphous phase containing Fe as the main component and an appropriate amount of Si, thereby completing the present invention.
[0011] That is, the gist of the present invention is as follows. (1) The following composition formula: Fe 100-x-y-z-w B x Ni y S z M w(In the formula, M is one or more inevitable elements selected from Nb, Mo, Ta, W, Co, and Sn; x, y, z, and w are in atomic %, and satisfy 12 ≤ x ≤ 17, 1 ≤ y ≤ 3, 0 < z ≤ 1, and 0 < w ≤ 0.1). The soft magnetic material is such that the soft magnetic material contains an α-Fe phase, the α-Fe phase contains crystals with an average particle size of 30 nm or less, and the average particle size of the crystals is the average value of the equivalent diameter of the projected area of the crystals in a transmission electron microscope (TEM) image of the soft magnetic material thinned by focused ion beam (FIB). The ratio (crystalline (211) plane peak area / XRD peak total area) of the peak area of the crystalline (211) plane to the total area of the peaks measured by XRD of the α-Fe phase on the surface of the soft magnetic material is 0.10 or more. (2) The soft magnetic material according to (1), wherein 0.2 ≤ z ≤ 0.9. (3) The following composition formula: Fe 100-x-y-z-w B x Ni y Si z M w (In the formula, M is one or more inevitable elements selected from Nb, Mo, Ta, W, Co, and Sn; x, y, z, and w are in atomic %, and satisfy 12 ≤ x ≤ 17, 1 ≤ y ≤ 3, 0 < z ≤ 1, and 0 < w ≤ 0.1). A method for producing a soft magnetic material includes preparing an alloy having the composition and having an amorphous phase, and rapidly heat-treating the alloy so that the reaching temperature of the alloy is in a temperature range that is equal to or higher than the crystal formation start temperature of the α-Fe phase and lower than the Fe-B compound formation start temperature. (4) The production method according to (3), wherein in the rapid heat treatment, the reaching temperature of the alloy is 485°C to 500°C. (5) The production method according to (3) or (4), wherein in the rapid heat treatment, the heating rate of the alloy is 100°C / second to 415°C / second. (6) The production method according to any one of (3) to (5), wherein in the rapid heat treatment, the holding time of the alloy is 0 second to 80 seconds. (7) The production method according to any one of (3) to (6), wherein the rapid heat treatment is carried out by sandwiching the heated block of the alloy.
Advantages of the Invention
[0012] The present invention provides a soft magnetic material that achieves both a high saturation magnetic flux density and a low coercive force, and a method for manufacturing the same.
Brief Description of the Drawings
[0013] [Figure 1] It is a graph showing the relationship between the Si content and (A) the peak area ratio of the crystalline (211) plane, or (B) the saturation magnetic flux density for Example 5 and Comparative Examples 5 to 6. [Diagram 2] It is a graph showing the relationship between the heat treatment temperature and the saturation magnetic flux density for Examples 1 to 7 and Comparative Examples 1 to 4. [Diagram 3] It is a graph showing the relationship between the peak area ratio of the crystalline (211) plane and the saturation magnetic flux density for Examples 1 to 7 and Comparative Examples 1 to 4.
Embodiments for Carrying Out the Invention
[0014] Hereinafter, preferred embodiments of the present invention will be described in detail. In this specification, the features of the present invention will be described with reference to the drawings as appropriate. The soft magnetic material and the manufacturing method thereof of the present invention are not limited to the following embodiments, and can be implemented in various forms with modifications, improvements, etc. that can be made by those skilled in the art without departing from the gist of the present invention.
[0015] In this specification, etc., a range expressed as "numerical value ~ numerical value" means a range including the said numerical values.
[0016] (Soft Magnetic Material) The soft magnetic material of the present invention is an Fe-based nanocrystalline soft magnetic material represented by the following composition formula: Fe 100-x-y-z-w B x Ni y Si z M w (wherein M is one or more inevitable elements selected from Nb, Mo, Ta, W, Co, and Sn, and x, y, z, and w are in atomic %, satisfying 12 ≦ x ≦ 17, 1 ≦ y ≦ 3, 0 < z ≦ 1, 0 < w ≦ 0.1).
[0017] The composition of the amorphous alloy does not usually change during the manufacturing process of the soft magnetic material of the present invention, and therefore the composition of the soft magnetic material of the present invention is the same as the composition of the amorphous alloy used in the manufacturing process.
[0018] In the soft magnetic material of the present invention, the main component is Fe, and the Fe content is 50 atomic % or more of the entire composition. Therefore, 100-xyzw, which indicates the Fe content, is 50 atomic % or more, and in one embodiment, is 80 or more, and in another embodiment, is 85 or more, from the viewpoint of having a high saturation magnetic flux density.
[0019] The content x of B (boron) is 12 to 17, and in one embodiment, 12 to 14, in atomic %.
[0020] By including B in the soft magnetic material of the present invention within the above range, the Fe content can be ensured, and the presence of B between α-Fe crystals suppresses the crystal grain growth of α-Fe, thereby maintaining the coercive force of the soft magnetic material low.
[0021] The Ni content, y, is in atomic % and is 1 to 3, and in one embodiment, 1.5 to 2.5.
[0022] When the soft magnetic material of the present invention contains Ni in the above range, the magnitude of the induced magnetic anisotropy can be controlled.
[0023] The content of Si, z, is in the range of more than 0 and not more than 1, in one embodiment, 0.2 to 0.9, and in another embodiment, 0.5 to 0.9, in terms of atomic %.
[0024] By containing Si in the above range, the soft magnetic material of the present invention can increase the peak area ratio of the (211) plane of the α-Fe phase on the surface of the soft magnetic material measured by XRD (X-Ray Diffraction).
[0025] M, i.e., w, which indicates the content of unavoidable elements, is in the range of more than 0 and not more than 0.1, and in one embodiment, in the range of more than 0 and not more than 0.05, in atomic %. Note that unavoidable elements refer to impurities, such as impurities contained in raw materials, the inclusion of which cannot be avoided, or impurities whose avoidance would result in a significant increase in production costs.
[0026] By including the unavoidable elements in the soft magnetic material of the present invention within the above ranges, it is possible to suppress a decrease in saturation magnetic flux density caused by an increase in the unavoidable elements.
[0027] In addition, the soft magnetic material of the present invention may contain one or more elements selected from the group consisting of, for example, Zr, Hf, Cu, Ag, Au, Zn, As, Sb, Bi, Y and rare earth elements, in order to improve corrosion resistance, suppress grain growth, and increase the frequency of nucleation, within a range that does not significantly reduce the saturation magnetic flux density.
[0028] In the soft magnetic material of the present invention, the ratio of the peak area of the crystalline (211) plane (crystalline (211) plane peak area) to the total peak area (total XRD peak area) measured by XRD of the α-Fe phase on the surface of the soft magnetic material (crystalline (211) plane peak area) (crystalline (211) plane peak area / total XRD peak area, hereinafter also referred to as "crystalline (211) plane peak area ratio") is 0.10 or more, in one embodiment 0.100 or more, in one embodiment 0.102 or more, and in one embodiment 0.105 or more. The crystalline (211) plane peak area ratio is not limited, but is usually 0.13 or less, and in one embodiment 0.12 or less.
[0029] Here, the peaks measured by XRD of the α-Fe phase on the surface of the soft magnetic material include the peaks of the (110), (200), (211), (220) and (310) planes, as is known in the art. Furthermore, the (110) and (211) planes each have a crystalline peak and an amorphous peak (halo peak). Therefore, the crystalline (211) plane peak area ratio in the present invention means the ratio of the peak area of the crystalline (211) plane to the total area of all peaks observed by XRD, that is, the crystalline (110) plane, the amorphous (110) plane, the (200) plane, the crystalline (211) plane, the amorphous (211) plane, the (220) plane and the (310) plane.
[0030] The crystalline (211) plane peak area ratio can be calculated as follows. (1) The X-ray diffraction pattern of the soft magnetic material is measured by XRD. (2) The obtained X-ray diffraction pattern is normalized by the peak of the (110) plane, which has the maximum intensity. (3) For each peak, the background (BG) is linearly approximated by the average value of 10 points at each end of the following 2θ ranges: 30° to 60° for the (110) plane, 60° to 70° for the (200) plane, 70° to 92° for the (211) plane, 94° to 102° for the (220) plane, and 112° to 120° for the (310) plane. (4) For each peak after subtracting BG, the crystalline peak and the amorphous peak are fitted using a split Pearson VII function, and the areas of Kα1 and Kα2 of each peak are calculated. In the soft magnetic material of the present invention, the halo peaks derived from the amorphous material are confirmed on the (110) and (211) planes. Therefore, the crystalline Kα1 and Kα2 and the amorphous Kα1 and Kα2 are observed on the (110) and (211) planes, respectively. (5) The crystalline (211) plane peak area ratio is calculated by dividing the Kα1 peak area of the crystalline (211) plane by the sum of the Kα1 peak areas of each peak.
[0031] The crystalline (211) plane peak area ratio of the soft magnetic material of the present invention falling within the above range means that the soft magnetic material of the present invention contains crystal grains in which the (211) plane, which is a specific crystal plane of the α-Fe phase, has grown anisotropically (has a uniform crystal orientation). Such crystal grains provide the soft magnetic material with low coercivity (low loss) and high saturation magnetic flux density (high torque).
[0032] The soft magnetic material of the present invention contains α-Fe phase crystals in an amount of 30% by volume or more, and in one embodiment 60% by volume or more, based on the total volume of the soft magnetic material.
[0033] The average grain size of the α-Fe phase crystals contained in the soft magnetic material of the present invention is 30 nm or less. The average grain size of the α-Fe phase crystals is not limited, but is usually 10 nm or more. Here, the average grain size of the α-Fe phase crystals is calculated by (1) cutting the soft magnetic material into thin slices using a focused ion beam (FIB), (2) observing the sliced soft magnetic material sample with a transmission electron microscope (TEM), (3) randomly selecting 100 or more crystals from the α-Fe phase in the TEM image, (4) measuring the projected area circle equivalent diameter (Heywood diameter) of the selected crystals as the grain size, and (5) averaging the obtained grain sizes.
[0034] When the average grain size of the α-Fe phase crystals contained in the soft magnetic material of the present invention is within the above range, a high saturation magnetic flux density and low coercive force of the soft magnetic material can be achieved.
[0035] When the soft magnetic material of the present invention is in the form of a thin ribbon, the average thickness of the soft magnetic material of the present invention is not limited, but is usually 10 μm to 25 μm, and in one embodiment, 15 μm to 30 μm.
[0036] By setting the thickness of the soft magnetic material of the present invention within the above range, loss can be reduced.
[0037] The saturation magnetic flux density of the soft magnetic material of the present invention is usually 1.850T or more, and in one embodiment, 1.855T or more, for example, 1.850T to 1.900T, and in one embodiment, 1.855T to 1.900T.
[0038] The coercive force of the soft magnetic material of the present invention is usually 20 A / m or less, and in one embodiment, 12 A / m or less, for example, 5 A / m to 20 A / m, and in one embodiment, 7.0 A / m to 12 A / m.
[0039] The soft magnetic material of the present invention has both a high saturation magnetic flux density and a low coercive force, and can be used as a core for electronic components such as motors and reactors.
[0040] (Method of manufacturing soft magnetic materials) The soft magnetic material of the present invention can be produced by a method known in the art, for example, the method described in JP 2019-206746 A, except that the raw alloy contains an appropriate amount of Si and the alloy is subjected to rapid heat treatment.
[0041] An example of a method for producing the soft magnetic material of the present invention will be described below. (Preparation process of amorphous alloy) First, an alloy having an amorphous phase is prepared. As described above, the alloy having an amorphous phase is a raw material of the soft magnetic material of the present invention, which has the same composition as the soft magnetic material of the present invention, and is mainly composed of Fe.
[0042] In the present invention, "the main component is Fe" means that the content of Fe in the material is 50 atomic % or more. "An alloy having an amorphous phase" means that the amorphous phase is present in an alloy at 50 volume % or more, and this is sometimes simply called "amorphous alloy". "Alloys" can be in the form of ribbons, flakes, granules, bulk, etc.
[0043] From the viewpoint of obtaining a large amount of fine crystalline phase by rapid thermal treatment, the content of the amorphous phase in the amorphous alloy is 60% by volume or more in one embodiment, and 85% by volume or more in another embodiment.
[0044] Amorphous alloys are obtained by quenching a molten metal whose main component is Fe. B promotes the formation of an amorphous phase when the molten metal is quenched. When the B content (residual amount of B) of the amorphous alloy obtained by quenching the molten metal is 12 atomic % or more of the entire composition, the main phase of the amorphous alloy can be made amorphous. On the other hand, when the B content of the amorphous alloy is 17 atomic % or less of the entire composition, the amount of Fe required for high saturation magnetic flux density can be secured, while the formation of Fe-B compounds during crystallization of the amorphous phase can be avoided.
[0045] The amorphous alloy contains Ni. The amorphous alloy contains Ni, which allows the magnitude of induced magnetic anisotropy to be controlled. From the viewpoint of clearly exerting the effect, the Ni content is 1 atomic % or more of the entire composition. On the other hand, if the Ni content is 3 atomic % or less of the entire composition, the other essential elements of the amorphous alloy, Fe and B, do not become excessively small, and as a result, the soft magnetic material obtained by rapid heat treatment of the amorphous alloy can achieve both high saturation magnetic flux density and low coercive force.
[0046] In the amorphous alloy, a portion of B is replaced by Si.
[0047] It has been known that Si is an element responsible for the formation of amorphous phase, and that the addition of Si increases the temperature at which Fe-B compounds with large crystalline magnetic anisotropy are formed, making it possible to increase the heat treatment temperature. In the present invention, it has been found that, unlike the conventional teaching, by adding an appropriate amount of Si, that is, in the range of more than 0 atomic % and not more than 1 atomic % of the entire composition, in one embodiment, 0.2 atomic % to 0.9 atomic %, and in another embodiment, 0.5 atomic % to 0.9 atomic %, the anisotropic growth of the crystal of the α-Fe phase, that is, the growth of the (211) plane of the crystal of the α-Fe phase, can be promoted by heat treatment, and a high saturation magnetic flux density can be expressed.
[0048] Furthermore, Si has the effect of lowering the viscosity of the molten metal, making it easier to eject the molten metal, and suppressing nozzle clogging.
[0049] In the amorphous alloy, the composition formula contains one or more unavoidable elements selected from the group consisting of Nb, Mo, Ta, W, Co, and Sn.
[0050] In addition, the amorphous alloy may contain one or more elements selected from the group consisting of, for example, Zr, Hf, Cu, Ag, Au, Zn, As, Sb, Bi, Y and rare earth elements in order to improve corrosion resistance, suppress grain growth, and increase the frequency of nucleation, within a range that does not significantly reduce the saturation magnetic flux density.
[0051] Next, the method for producing the amorphous alloy will be described. As long as the amorphous alloy having the composition represented by the above composition formula can be obtained, there is no limitation on the method for producing the amorphous alloy. As described above, the alloy has a form such as a ribbon, a flake, a granule, and a bulk. In order to obtain a desired form, the method for producing the amorphous alloy can be appropriately selected.
[0052] As a method for producing an amorphous alloy, for example, an ingot containing a composition represented by the above-mentioned composition formula is prepared in advance, and the ingot is melted to obtain a molten metal, which is then rapidly cooled to obtain an amorphous alloy. When an element is depleted during melting of the ingot, an ingot having a composition that takes into account the amount of the element depleted is prepared. When the ingot is crushed and melted, it is preferable to subject the ingot to a homogenization heat treatment before crushing.
[0053] The molten metal may be rapidly cooled by a conventional method, such as a single roll method using a cooling roll made of copper or a copper alloy. The peripheral speed of the cooling roll in the single roll method may be a standard peripheral speed for producing an amorphous alloy whose main component is Fe. The peripheral speed of the cooling roll may be, for example, usually 15 m / sec to 55 m / sec.
[0054] The temperature of the molten metal when it is discharged onto the single roll is usually 50° C. to 300° C. higher than the melting point of the ingot. There is no particular limitation on the atmosphere when the molten metal is discharged, but from the viewpoint of reducing the inclusion of oxides and the like in the amorphous alloy, an atmosphere of an inert gas or the like is preferable.
[0055] (Process for rapid heat treatment of amorphous alloy) Next, the amorphous alloy is subjected to rapid heat treatment. Rapid heat treatment means that the amorphous alloy is rapidly heated to a predetermined temperature range, held for a short time, and then rapidly cooled. Specifically, the amorphous alloy is heated from a temperature higher than the crystallization start temperature of the α-Fe phase or, in one embodiment, a temperature higher than the crystallization start temperature of the α-Fe phase, for example, a temperature higher by 100° C. in one embodiment, a temperature higher by 150° C. in one embodiment, or a temperature higher by 200° C. in one embodiment, as described below, to a temperature range lower than the Fe-B compound generation start temperature at a temperature increase rate of usually 100° C. / sec or more, held in the temperature range for 0 to 80 seconds, and then cooled at a temperature decrease rate of usually 100° C. / sec or more.
[0056] If the heating rate is generally 100° C. / sec or more, the crystal phase will not become coarse. From the viewpoint of avoiding the coarsening of the crystal phase, a faster heating rate is preferable, and the heating rate is 150° C. / sec or more in one embodiment, and 325° C. / sec or more in one embodiment. On the other hand, if the heating rate is very fast, the heat source for heating becomes too large, which impairs economic efficiency. From the viewpoint of the heat source, the heating rate is 415° C. / sec or less in one embodiment. The heating rate may be the average rate from the start of heating to the start of holding. When the holding time is 0 seconds, the heating rate may be the average rate from the start of heating to the start of cooling. Alternatively, the heating rate may be the average rate in a certain temperature range, for example, between 100° C. and 500° C.
[0057] If the holding time is 0 seconds or more, a fine crystalline phase is obtained from the amorphous phase. The holding time of 0 seconds means that the temperature is rapidly increased, followed by immediate cooling or terminating the holding. In one embodiment, the holding time is 3 seconds or more. On the other hand, if the holding time is 80 seconds or less, coarsening of the crystalline phase can be avoided. From the viewpoint of avoiding coarsening of the crystalline phase, the holding time is 60 seconds or less in one embodiment, and 10 seconds or less in one embodiment.
[0058] If the heat treatment temperature (holding temperature) is equal to or higher than the crystal formation start temperature of the α-Fe phase, the amorphous phase can be made into a crystalline phase and the nanocrystalline structure can be stabilized. On the other hand, if the holding temperature is equal to or higher than the Fe-B compound formation start temperature, the Fe-B compound is formed, and strong crystalline magnetic anisotropy occurs, resulting in an increase in coercive force. Therefore, by setting the holding temperature to be lower than the Fe-B compound formation start temperature, the crystal phase can be refined without forming the Fe-B compound. Therefore, the heat treatment temperature is equal to or higher than the crystal formation start temperature of the α-Fe phase, and in one embodiment, as described below, it is a temperature range from a temperature higher than the crystal formation start temperature of the α-Fe phase to a temperature lower than the Fe-B compound formation start temperature. In one embodiment, the heat treatment temperature is usually 485°C to 500°C. The crystal formation start temperature of the α-Fe phase and the Fe-B compound formation start temperature may vary depending on the alloy system, but can be measured, for example, by DSC measurement. The heat treatment temperature is the temperature that the amorphous alloy reaches by heat treatment.
[0059] The heating method is not particularly limited as long as it is possible to heat the amorphous alloy at the heating rate described above.
[0060] When a conventional atmospheric furnace is used, the heating rate and / or holding temperature of the atmosphere within the furnace can be higher than the desired heating rate and / or holding temperature for the amorphous alloy.
[0061] When an infrared furnace is used instead of a normal atmospheric furnace, the time lag between the amount of heat input to the infrared heater and the amount of heat received by the amorphous alloy can be reduced. Note that an infrared furnace is a furnace that reflects the light emitted by an infrared lamp with a concave surface to rapidly heat the heated object.
[0062] Additionally, the amorphous alloy may be rapidly heated and held at a desired temperature by solid-to-solid heat transfer, for example by sandwiching the amorphous alloy between blocks that have already been heated to a desired holding temperature.
[0063] The cooling rate of the soft magnetic material is usually 100° C. / sec or more, and in one embodiment, 100° C. / sec to 415° C. / sec, so that the crystal phase does not become further coarsened.
[0064] Without being bound by theory, it is believed that when an amorphous alloy is subjected to rapid heat treatment, the following phenomenon occurs within the amorphous alloy.
[0065] The amorphous alloy is rapidly heated to a temperature range equal to or higher than the crystallization temperature of the α-Fe phase and is held at that temperature range for a short period of time, which is believed to prevent the microstructure of the crystalline phase from becoming coarse and result in a fine crystalline phase.
[0066] Here, the size of the microstructure depends on the heterogeneous nucleation rate, which is governed by atomic transport and the size of the critical nucleus.
[0067] In order to refine the microstructure, it is considered that the heterogeneous nucleation rate should be increased, and in order to increase the heterogeneous nucleation rate, the atomic transport should be increased and the size of the critical nucleus should be reduced. In order to achieve these two conditions, it is effective to introduce a supercooled liquid region in an amorphous body. Since the viscous flow is very large in the supercooled liquid region in an amorphous body, the strain energy due to nucleation in the supercooled liquid is much smaller than the strain energy due to nucleation in an amorphous body. Therefore, many embryos become nuclei in the supercooled liquid region.
[0068] In conventional heat treatment (annealing), however, the crystallization of the amorphous phase starts at a relatively low temperature due to the slow heating rate, and therefore the transition from solid to supercooled liquid is limited at relatively low temperatures, and heterogeneous nucleation is also very limited.
[0069] In contrast, when the amorphous alloy is heated at a rapid temperature rise as in the present invention, the crystallization start temperature of the α-Fe phase can be increased. Then, the amorphous phase can maintain the amorphous state up to a high temperature where the amorphous phase actively transitions to a supercooled liquid. When the amorphous phase transitions to a supercooled liquid, atomic transport increases, the size of the critical nucleus decreases, and the heterogeneous nucleation rate increases. As a result, the nucleation frequency also increases.
[0070] Therefore, by rapidly heating the amorphous alloy, high atomic transport can be achieved in the region where the supercooled liquid is formed, and vigorous nucleation can occur.
[0071] On the other hand, when the temperature of an amorphous alloy is increased rapidly, the grain growth rate also increases. In the present invention, the holding time is short, so that the time for grain growth is shortened and the grain growth is suppressed.
[0072] In addition, in the crystallization process, if the thermal energy given to the amorphous alloy is insufficient (for example, the heat treatment temperature is low, etc.), the diffusion of atoms in the amorphous alloy becomes insufficient, and the heat treatment ends in an unstable state. In that case, for example, when the obtained soft magnetic material is used in a high-temperature environment, the thermal energy given from the usage environment causes the movement of atoms in the material, changing the short-range structure of the material, and as a result, the magnetic properties of the material may decrease, for example, the coercive force of the material may increase.
[0073] Therefore, the alloy having an amorphous phase is heated to a temperature equal to or higher than the crystallization start temperature of the α-Fe phase, particularly to a temperature that is usually 100° C. to 200° C. higher than the crystallization start temperature of the α-Fe phase, and in one embodiment, 100° C. to 150° C. higher than the crystallization start temperature of the α-Fe phase. This allows sufficient diffusion of atoms in the amorphous alloy, and for example, even when the obtained soft magnetic material is used in a high-temperature environment, the movement of atoms (mainly the movement of B atoms) due to thermal energy applied from the usage environment is suppressed, and as a result, the magnetic properties of the material, particularly the coercive force, are stabilized at a low level.
[0074] On the other hand, when the temperature of the amorphous alloy reaches the temperature at which the Fe-B compound begins to form, the Fe-B compound is formed. The Fe-B compound has a large crystal magnetic anisotropy, which increases the coercive force.
[0075] Therefore, by heating the amorphous alloy to a temperature below the temperature at which the Fe-B compound formation begins, the formation of the Fe-B compound can be suppressed and the properties, particularly the magnetic properties, can be maintained at a good level. EXAMPLES
[0076] Several examples of the present invention will be described below, but it is not intended that the present invention be limited to those shown in these examples.
[0077] (Preparation of amorphous alloys) The raw materials were weighed and arc-melted to produce ingots so as to obtain the composition shown in Table 1. The raw materials used were pure Fe, Fe-B alloy, pure Ni, etc. In this process, the ingots were repeatedly melted (3 to 5 times) by turning over so as to obtain a homogeneous ingot.
[0078] The finely cut ingot was loaded into the nozzle of a liquid quenching device (single roll method) and melted by high-frequency heating in an inert atmosphere to obtain a molten metal. The molten metal was then discharged onto a copper roll with a peripheral speed of 30 m / s to 70 m / s and quenched to obtain a ribbon-shaped amorphous alloy with a width of 5 mm. The temperature during discharge was melting point + 50°C to 200°C. The quenching conditions were adjusted by setting the gap at 0.4 mm and controlling the chamber internal pressure and nozzle internal pressure so that the discharge pressure was 40 kPa to 80 kPa.
[0079] Incidentally, the amorphous alloy was confirmed to be amorphous by XRD before the heat treatment described below, and the composition was confirmed by ICP.
[0080] (Heat treatment of amorphous alloys) An amorphous alloy having the composition shown in Table 1 was sandwiched between a heating plate (made of stainless steel) and a calcium silicate plate, which had been heated so that the temperature of the amorphous alloy reached the heat treatment temperature shown in Table 1, in a configuration of heating plate-amorphous alloy-calcium silicate plate, and then heated for 3 seconds, and then rapidly cooled by removing the plate from the heating plate. This heating crystallized the amorphous phase in the amorphous alloy, and a sample of a soft magnetic material was obtained. The heating rate was 100°C / sec or more, and the cooling rate was 100°C / sec.
[0081] (Sample Evaluation) XRD (apparatus: Rigaku Smart LabII) analysis was performed on the samples after each heat treatment under the conditions shown in Table 2, and the area ratio of each peak of the α-Fe phase was calculated. The area ratio of each peak was calculated according to the method described above. Then, the coercive force and saturation magnetic flux density of the samples after each heat treatment were measured using a VSM (vibrating sample magnetometer)-P2H type-Helmholtz coil 2000e (manufactured by Toei Kogyo Co., Ltd.).
[0082] The results are shown in Table 1 and Figures 1 to 3. Figure 1 shows the relationship between the Si content and (A) the crystalline (211) plane peak area ratio or (B) the saturation magnetic flux density for samples (Example 5 and Comparative Examples 5 to 6) with a heat treatment temperature of 490°C. Figure 2 shows the relationship between the heat treatment temperature and the saturation magnetic flux density for samples (Examples 1 to 7 and Comparative Examples 1 to 4) with a Si content of 0.8 atomic %. Figure 3 shows the relationship between the crystalline (211) plane peak area ratio and the saturation magnetic flux density for samples with a Si content of 0.8 atomic %.
[0083] [Table 1]
[0084] [Table 2]
[0085] In Table 1, amo indicates an amorphous peak. From Table 1 and FIG. 1, it was found that the saturation magnetization can be improved by increasing the crystalline (211) plane peak area ratio by adding an appropriate amount of Si. Furthermore, from Table 1 and FIG. 2, it was found that the crystalline (211) plane peak area ratio can be controlled by rapid heat treatment, particularly the heat treatment temperature, during the production of the soft magnetic material of the present invention. Furthermore, from Table 1 and FIG. 3, it was found that in the soft magnetic material of the present invention, the saturation magnetization can be improved by increasing the crystalline (211) plane peak area ratio.
Claims
1. The composition formula: Fe 100-x-y-z-w B x Yes y Yes z M w (In the formula, M is one or more unavoidable elements selected from Nb, Mo, Ta, W, Co, and Sn, and x, y, z, and w satisfy, in atomic %, 12≦x≦17, 1≦y≦3, 0<z≦1, and 0<w≦0.1.) A soft magnetic material represented by the formula: the soft magnetic material includes an α-Fe phase; The α-Fe phase contains crystals having an average grain size of 30 nm or less; The average grain size of the crystals is an average value of the diameters of circles equivalent to the projected area of the crystals in a transmission electron microscope (TEM) image of the soft magnetic material sliced by a focused ion beam (FIB), The ratio of the peak area of the crystalline (211) plane to the total peak area of the α-Fe phase on the surface of the soft magnetic material measured by XRD is 0.10 or more. Soft magnetic material.
2. 2. The soft magnetic material according to claim 1, wherein 0.2≦z≦0.
9.
3. The following composition formula: Fe 100-x-y-z-w B x Ni y S z M w (In the formula, M is one or more unavoidable elements selected from Nb, Mo, Ta, W, Co, and Sn, and x, y, z, and w satisfy, in atomic %, 12≦x≦17, 1≦y≦3, 0<z≦1, and 0<w≦0.1.) Preparing an alloy having an amorphous phase and a composition represented by the formula: The alloy is subjected to rapid heat treatment so that the temperature of the alloy reaches a temperature range equal to or higher than the crystal formation start temperature of the α-Fe phase and lower than the formation start temperature of the Fe-B compound. A method for producing a soft magnetic material comprising the steps of:
4. The method according to claim 3, wherein the temperature reached by the alloy in the rapid thermal treatment is 485°C to 500°C.
5. The method according to claim 4, wherein the heating rate of the alloy in the rapid thermal treatment is 100° C. / sec to 415° C. / sec.
6. The method according to claim 5, wherein the holding time of the alloy in the rapid thermal treatment is 0 to 80 seconds.
7. A method according to any one of claims 3 to 6, wherein the rapid thermal treatment is carried out by sandwiching the alloy between heated blocks.
Citation Information
Patent Citations
Novel iron-based amorphous nanocrystalline magnetically soft alloy and preparation method thereof
CN109295401A
Fe-BASED AMORPHOUS ALLOY THIN STRIP AND MAGNETIC CORE
JP2006045660A
Plural flat magnetic metal particles, powder material, and rotating electric machine
JP2020025077A
Method of manufacturing magnetic component
JP2020084270A
Metallic strip, method for producing amorphous metallic strip, and method for producing nanocrystal metallic strip
JP2021037543A